Geographical distribution and profile of medical doctors in public sector hospitals of the Limpopo Province, South Africa - Samuel T. Ntuli; Edwin Maboya (AOSIS, 2017)
Background: The shortage and unequal distribution of medical doctors in low- and middle-income countries continues to be a public health concern. Objective: To establish the geographical distribution and demographic profile of medical doctors in public sector hospitals of the Limpopo Province, South Africa. Method: The PERSAL system was used to obtain information on the number of medical doctors employed in public sector hospitals of the Limpopo Province. Data were exported from PERSAL's database and then analysed using STATA version 9.0. Result: The mean age of the 887 medical doctors was 40.1 ± 11.2 years (range 24-79 years). Sixty per cent of the doctors were male, 66% were aged ≤ 45 years and 84% were African. Most of the doctors (86%) were medical officers, of which 55% had < 5 years working experience. Overall, the doctor-to-population ratio for the five districts in the province was 16.4/100 000, with Capricorn (33.7/100 000) and Waterberg (20.2/100 000) recording the highest ratios. A large proportion (43%) of medical officers are employed in the Capricorn District, of which 71% were practising at the tertiary hospital. Conclusion: This study demonstrated a shortage and maldistribution of medical doctors in the public sector hospitals of the Limpopo Province. This has a potentially negative effect on the delivery of an appropriate and efficient healthcare service to the population and requires urgent attention.